Leaf-cutter ants – mycorrhizal fungi: observations and research questions from an unexpected mutualism - Michael F. Allen; Hannah Shulman; Philip W. Rundel; Thomas C. Harmon; Emma L. Aronson (Frontiers in Fungal Biology, 2023)
Leaf-cutter ants (LCAs) are widely distributed and alter the physical and biotic architecture above and below ground. In neotropical rainforests, they create aboveground and belowground disturbance gaps that facilitate oxygen and carbon dioxide exchange. Within the hyperdiverse neotropical rainforests, arbuscular mycorrhizal (AM) fungi occupy nearly all of the forest floor. Nearly every cubic centimeter of soil contains a network of hyphae of Glomeromycotina, fungi that form arbuscular mycorrhizae. Our broad question is as follows: how can alternative mycorrhizae, which are—especially ectomycorrhizae—essential for the survival of some plant species, become established? Specifically, is there an ant–mycorrhizal fungus interaction that facilitates their establishment in these hyperdiverse ecosystems? In one lowland Costa Rican rainforest, nests of the LCA Atta cephalotes cover approximately 1.2% of the land surface that is broadly scattered throughout the forest. On sequencing the DNA from soil organisms, we found the inocula of many AM fungi in their nests, but the nests also contained the inocula of ectomycorrhizal, orchid mycorrhizal, and ericoid mycorrhizal fungi, including Scleroderma sinnamariense, a fungus critical to Gnetum leyboldii, an obligate ectomycorrhizal plant. When the nests were abandoned, new root growth into the nest offered opportunities for new mycorrhizal associations to develop. Thus, the patches created by LCAs appear to be crucial sites for the establishment and survival of shifting mycorrhizal plant–fungal associations, in turn facilitating the high diversity of these communities. A better understanding of the interactions of organisms, including cross-kingdom and ant–mycorrhizal fungal interactions, would improve our understanding of how these ecosystems might tolerate environmental change.